Routledge Handbook of Contemporary Indonesia - Wahyu Susilo (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2021)
This review of Robert F Hefner's book begins with the relevance of this book's cover to the current pros and cons regarding school uniforms and their relation to religion. This book was published when issues and religious symbols strengthened in the electoral process in Indonesia, at least in the 2014 elections and the DKI Regional Head Elections. Even though the proponent of this issue lost, the influence of Islam in the way of life of the state is getting stronger. In historical terms, Islam has always been an important factor in socio-political life since the Dutch East Indies to Indonesia today. Studies on the Dutch East Indies (Indology) to studies on Indonesia (Indonesia studies) always place Islam as a strong variable. Starting from Snouck Hurgonje to Cliford Geertz who was a pioneer in the study of Islam and their work became a reference for subsequent studies. Hefner's edited book contributes to showing the role and influence of Islam in contemporary Indonesia, especially after the reformation. Although not specifically reviewing Islam and Indonesia, all existing analyzes on democracy, law, politics, and socio-cultural aspects related to media, entertainment and ethnicity are closely related to Islam, as well as gender and plural society.